PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK KELAS V PADA PEMBELAJARAN IPA DI MI 01 NW BAGIK PAYUNG - Hilman; Parhan; Alfandi (Jurnal Ikhtibar Nusantara, 2026)
This study was motivated by the limited number of studies investigating the implementation of Problem-Based Learning (PBL) to improve elementary school students' critical thinking skills, particularly in science learning on the topic of Changes in the States of Matter in Islamic elementary schools (Madrasah Ibtidaiyah). Although critical thinking is recognized as one of the essential competencies required in the twenty-first century, many elementary school students still demonstrate insufficient critical thinking skills, highlighting the need for innovative and student-centered instructional approaches. Therefore, this study aimed to examine the effect of the Problem-Based Learning (PBL) model on the critical thinking skills of fifth-grade students at MI 01 NW Bagik Payung in science learning. This study employed a quantitative approach using a one-group pretest-posttest design. The participants consisted of 22 fifth-grade students, selected through a saturated sampling technique. Data were collected using a critical thinking skills test administered before (pre-test) and after (post-test) the implementation of the Problem-Based Learning model. The collected data were analyzed using a paired-samples t-test to determine the significance of the difference between the pre-test and post-test scores. The findings revealed that the implementation of the Problem-Based Learning model significantly improved students' critical thinking skills. This improvement was reflected in the increase in the mean score from 55.68 on the pre-test to 86.69 on the post-test. Furthermore, the hypothesis testing yielded a t-value of 12.376, which exceeded the critical t-value of 1.724, indicating a statistically significant effect of the Problem-Based Learning model on students' critical thinking skills. These findings support the study's objective and reinforce Piaget's constructivist theory, which emphasizes that knowledge is actively constructed through learners' engagement in problem-solving activities. In conclusion, the Problem-Based Learning model is effective in enhancing the critical thinking skills of fifth-grade students in science learning at MI 01 NW Bagik Payung. Theoretically, this study contributes to the growing body of literature on the effectiveness of Problem-Based Learning in fostering higher-order thinking skills. Practically, it provides recommendations for teachers to adopt the Problem-Based Learning model as an alternative instructional strategy for promoting student-centered science learning. In addition, this study offers directions for future research to investigate the effectiveness of Problem-Based Learning across different educational levels, subject areas, and other learning outcome variables